The Role Of Consumer Ethnocentrism In Mediating The Influence Of E-Wom On Brand Equity (Study On Shopee And Bukalapak) - Syah, Mohammad Prima Aldebaran; Widodo, Teguh (UNIVERSITAS PAKUAN, 2019)
The rapid development of digitalization makes it easier for people to shop online through e-commerce. Indonesia ranked first with 88.1% of internet users using e-commerce. During the pandemic, e-commerce grew by 33.2% from 253 trillion to 337 trillion. Shopee is the first ranked e-commerce platform in Indonesia with the highest visits, while Bukalapak has the lowest visits. This difference is influenced by word of mouth between consumers. Electronic word of mouth influences the attitudes and decisions of internet users towards an e-commerce brand. User reviews indicate that Shopee has a negative e-WOM, while Bukalapak has a positive e-WOM. User trust in the brand and the consumer experience affect public opinion and brand equity. Further research is needed to examine the influence of ethnocentrism on brand equity and the factors that influence it, such as e-WOM. This study aims to determine the extent to which the influence of e-WOM on consumer ethnocentrism and brand equity applies to one e-commerce service, namely Shopee and Bukalapak. Research methods with quantitative research types and cross-sectional study designs Data collection is done directly with the type of primary data using questionnaires in the form of Google Forms, and the scale of measurement is the Likert scale. The population and sample in this study are Shopee and Bukalapak e-commerce users. The sampling technique uses non-probability sampling with purposive sampling. Data analysis was done by structural Equation modeling (SEM) and the SmartPLS program for data processing.